Polish Women Mathematicians: A Narrative Study of Women’s Career Paths in Academia - Wenderlich, Maja (Przegląd Badań Edukacyjnych (Educational Studies Review), 2025)
The aim of this article is to identify the factors that determine the development of the mathematical careers of the surveyed women. The analysis is based on the narratives of 14 outstanding female mathematicians who shared their professional and educational experiences. The study was qualitative in nature and was based on the semi-structured interview method. The selection of participants was purposeful, focused on women with recognised scientific achievements. Ten of them pursue scientific careers in Poland and four in the United States. The analysis takes into account both institutional and sociocultural factors influencing the formation of professional trajectories. The results of the study show that despite formal equal opportunities, women still encounter structural and cultural barriers in the exact sciences. Their individual development strategies, support from their environment, and institutional involvement turn out to be crucial for overcoming limitations and achieving scientific success.